2016
DOI: 10.3389/fnins.2016.00228
|View full text |Cite
|
Sign up to set email alerts
|

In utero and Lactational Exposure to Acetamiprid Induces Abnormalities in Socio-Sexual and Anxiety-Related Behaviors of Male Mice

Abstract: Neonicotinoids, a widely used group of pesticides designed to selectively bind to insect nicotinic acetylcholine receptors, were considered relatively safe for mammalian species. However, they have been found to activate vertebrate nicotinic acetylcholine receptors and could be toxic to the mammalian brain. In the present study, we evaluated the developmental neurotoxicity of acetamiprid (ACE), one of the most widely used neonicotinoids, in C57BL/6J mice whose mothers were administered ACE via gavage at doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 53 publications
(75 reference statements)
1
65
0
Order By: Relevance
“…Similar significant behavioral effects were detected with exposure to nicotine (Crosby et al 2015). Other studies using mice have also found effects on anxiety behaviors with exposure to clothianidin or acetamiprid, but in these studies anxiety was either increased (Hirano et al 2015) or decreased (Sano et al 2016). It is possible that the frogs may be highly anxious and resort to the preferred cryptic response instead of the less preferred flight response or have reduced anxiety and thus do not feel the need to flee.…”
Section: Discussionmentioning
confidence: 67%
“…Similar significant behavioral effects were detected with exposure to nicotine (Crosby et al 2015). Other studies using mice have also found effects on anxiety behaviors with exposure to clothianidin or acetamiprid, but in these studies anxiety was either increased (Hirano et al 2015) or decreased (Sano et al 2016). It is possible that the frogs may be highly anxious and resort to the preferred cryptic response instead of the less preferred flight response or have reduced anxiety and thus do not feel the need to flee.…”
Section: Discussionmentioning
confidence: 67%
“…However, increasing evidence to the contrary [11,12,13,14,15,16,17,18,19], and consideration of some neonicotinoid metabolites showing high affinities for mammalian nAChRs [3], suggests that neonicotinoids have potential developmental neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to IMI alters learning performance and related gene expression in infant and adult rats [16]. Recently, Sano et al reported that exposure to low dose ACE in utero and through lactation induces abnormalities in socio-sexual and anxiety-related behaviors in male mice [17]. Additionally, an in vivo mouse study revealed that four types of neonicotinoids (ACE, IMI, thiacloprid, and nitenpyram) readily pass through the blood–brain barrier (BBB) and are detectable in the brain at 60%–70% of the serum concentration within 15 min of intraperitoneal administration [18].…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning of the trial, the mouse was introduced in the dark compartment. The latency to enter the light compartment and the cumulative time spent in the light compartment were measured by an automated video tracking system (ANY-maze, Stoelting, USA) (Sano et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Three trials were performed, each lasting 30 min. The number of attempted mounts, mounts, and intromissions was scored for each mouse (Sano et al, 2016).…”
Section: Methodsmentioning
confidence: 99%